Idealisasi Tafsir Al-Ibriz Di Jawa - Abd. Majid Abror; Sayyidah Fatimah Z. (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
This research is a literature that explores Javanese interpretation. The results of the research conclude as follows: First, Javanese society is a society that lives within the confines of Javanese culture. The cultural traditions of the Javanese people in this area are still very strong with Javanese or traditional culture and customs. In principle, Javanese society is a religious society, namely a society that has the awareness to embrace a religion. Second, Tafsir Al-Ibriz neutralizes the Arabist emotions of the Koranic text into Javanese cosmology. Because al-Ibriz used Javanese, exploring the ins and outs of Javanese locality was his test tool. The condition of society in Java is still very much connected with authenticity and peace between citizens and families. Even without any foreign cultural background, typical Javanese society is still stable and inclusive of the traditions brought by their ancestors. The hope is that this can be a stepping stone for Tafsir al-Ibriz to be able to reach the ideal point as expected by his Mushonnif.